Limberg Flap Reconstruction in Treating Sacrococcygeal Pilonidal Sinus - Faruk, Md Omar; Sheikh, Md Shahadot Hossain; Parvin, Mst Maksuda; Siddiquee, Muhammad Ali; Bhuiyan, Md Jahangir Hossain; Aziz, Mohammad Mohibul (Bangladesh Journal of Medical Science, 2019)
Background: Pilonidal sinus is the relatively common condition affecting men almost twice as often as the women we experienced. The estimated incidence is 0.26 per thousand populations in general. The management of pilonidal sinus disease remains controversial, and gold standard treatment modality has yet to be established. Limberg procedure is a safe and reliable technique in the treatment of the sacrococcygeal pilonidal sinus disease, with a low complication and recurrence rates if performed according to the appropriate surgical principles. Methods: This is a Prospective study on 24 patients between the period from July 2014 to Dec 2018 in the Department of Surgery in Bangabandhu Sheikh Mujib Medical University (BSMMU) as well as other different hospitals in Dhaka, Bangladesh. The patients having primary or recurrent pilonidal sinus disease underwent the foresaid surgical treatment. Results: Twenty four patients underwent this operation. Among them, the picture was that 20(83.3%) were males and 4(16.7%) were female. The mean age was 31, (Range: 17-45 years). 6(25%) patients were presented with recurrent sinus and 5 of them had one or more occasion previous surgery. Twenty one patients (87.5%) had full primary healing without any complication. But 1(4.2%) patient had minimal seroma, 1(4.2%) patient had superficial infection and the remaining other 1(4.2%) had partial flap necrosis. However, all three healed completely with conservative treatment. The mean length of hospital stay was 2.45 (Range: 1-5) days and the most patients returned to their work within 3 weeks. Conclusion: Limberg flap is very effective for sacrococcygeal pilonidal sinus disease with low complication rates, shorter hospital stay, low recurrence rates, earlier healing and reduced off-work period. The surgery can be easily mastered. We recommend Limberg flap as preferred surgery in the cases of Sacrococcygeal Pilonidal sinus. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.105-109